(untitled) (Global Journal of Science Frontier Research, 2024)
The unsteady turbulent swirled water flow in a channel in the presence of cavitation is calculated The comparison of two forms of corrections to the k- -model of turbulence taking into account the swirl of the flow is performed as applied to the problem of calculating hydrodynamic oscillation generators It is shown that both considered corrections it made possible to achieve agreement between the calculated and experimental data on the pressure distribution along the wall of the generator channel and on the form of the amplitude-frequency characteristics of oscillations At the same time the linear correction it made possible to improve the stability of the calculation procedure and prevent the appearance of zones with non-physical negative pressures which in some cases were obtained using a quadratic correction The results obtained can be used in mathematical modeling of hydrodynamic oscillation generators for various purposes particularly for chemical technologies oil production and medicine